Tool use as distributed cognition: how tools help, hinder and define manual skill - Baber, Chris; Cengiz, Tulin G.; Parekh, Manish (Frontiers in Psychology, 2014)
Our thesis in this paper is that, in order to appreciate the interplay between cognitive (goal-directed) and physical performance in tool use, it is necessary to determine the role that representations play in the use of tools. We argue that rather being solely a matter of internal (mental) representation, tool use makes use of the external representations that define the human-environment-tool-object system. This requires the notion of Distributed Cognition to encompass not simply the manner in which artefacts represent concepts but also how they represent praxis. Our argument is that this can be extended to include how artefacts-in-context afford use and how this response to affordances constitutes a particular form of skilled performance. By artefacts-in-context, we do not mean solely the affordances offered by the physical dimensions of a tool but also the interaction between the tool and the object that it is being used on. From this, ‘affordance’ does not simply relate to the physical appearance of the tool but anticipates subsequent actions by the user directed towards the goal of changing the state of the object and this is best understood in terms of the ‘complimentarity’ in the system. This assertion raises two challenges which are explored in this paper. The first is to distinguish ‘affordance’ from the adaptation that one might expect to see in descriptions of motor control; when we speak of ‘affordance’ as a form of anticipation, don’t we just mean the ability to adjust movements in response to physical demands? The second is to distinguish ‘affordance’ from a schema of the tool; when we talk about anticipation, don’t we just mean the ability to call on a schema representing a ‘recipe’ for using that tool for that task? This question of representation, specifically what knowledge needs to be represented in tool use, is central to this paper.don